APPLICATION OF HARDWARE CAPITAL THERAPY TO IMPROVE THE QUALITY OF LIFE WITH HYPERTENSION IN THE AREA OF PUSKESMAS ROWOSARI SEMARANG - Ns. Diana Dayaningsih; Siswanto, Siswanto (Pusat Riset dan Inovasi Nasional, 2021)
Hypertension is a condition in which a person experiences an increase in blood pressure above normal which is prone to occur in the elderly, thereby reducing the quality of life of the elderly. Gardening therapy is one of the modalities of therapy that aims to improve the quality of life. This case study aims to describe the application of gardening modality therapy to improve the quality of life of the elderly with hypertension. This case study method uses a descriptive method involving 2 subjects with cooperative elderly criteria, the elderly aged > 60 years and having a history of hypertension (systolic blood pressure 140 mmHg and diastolic blood pressure > 90mmHg). The results of this case study indicate an improvement in the quality of life of the elderly. between before and after gardening therapy was carried out for 2 weeks. Subject I experienced an increase in quality of life from sufficient, namely 85 to good, namely 98. Meanwhile, subject II increased quality of life from sufficient, namely 86 to good, namely 105. The conclusion of this case study is that gardening therapy is effective in improving the quality of life of the elderly with hypertension in both subjects. Gardening therapy is highly recommended as a nursing intervention in hypertension management in the elderly with hypertension